Media Video Company Profile Sebagai Sarana Informasi Dan Promosi Pada PT Putra Karya Jasa Usaha - Sunarya, Lusyani; Febrianto, Mochammad; Salsabil, Qathrunnada (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Video media is the most important part for entrepreneurs, one of which is video media that can describe a company's identity, such as a company profile. This video simultaneously provides information and promotions to the market the company wants. One company that requires a company profile is PT. Putra Karya Jasa Usaha, namely an autobus company with a head office named Putra KJU, which is headquartered in the Commercial Lot, Jl. Citra Raya Boulevard No. 4, Tangerang Regency. The problem is, previously the media only used social media and print media, the concept of which was very simple. Since the 2020 pandemic, there has been a decrease in relations by 18.8% and the number of passengers has decreased by 61.6%. In contrast, the company had 16 associations in the previous year, as well as 751,463 passengers in a year. This motivated Putra KJU to make a company profile video as a promotional and information medium to provide an overview of the profile and services they offer to prospective passengers or clients. The method for making a company profile video is data collection, media design, and the Media Production Concept (KPM). Through this company profile video, Putra KJU can introduce corporate identity and help with marketing so that it is better known to many people.